Sejarah dan Perkembangan Regulasi Mengenai Perbankan Syariah Dalam Sistem Hukum Nasional Di Indonesia - Shandy Utama, Andrew (Sekolah Tinggi Hukum Bandung, 2018)
Islamic bank is a bank that runs its business activities based on sharia principles. At the time of the economic crisis of 1998, many conventional banks collapse while Islamic banks are not affected. After the crisis, Islamic banking experienced significant growth in Indonesia. The problem discussed in this research is how is the history and development of regulation on Islamic banking in national legal system in Indonesia? The method used in this research is normative legal research by using approach of legislation. Sources of data used in this research are secondary data, namely data obtained from legislation, scientific journals, and legal literature. Data collection techniques used in this research is literature study. Data analysis technique used in this research is qualitative analysis. The result of this research is that the initiative on establishment of Islamic bank in Indonesia was started since 1990 by the Indonesian Council of Ulama, which was realized with the establishment of Bank Muamalat Indonesia on November 1, 1991. The early development of Islamic banking in the national banking system was responded quickly by the government with the enactment of Act Number 7 of 1992 about Banking, which was later amended by Law Number 10 of 1998. In addition to being a devastation to the national banking system, the economic crisis that occurred in 1998 also became the starting point for the development of Islamic banking in Indonesia. Some conventional banks began to expand their business by establishing Islamic banks. Responding to the development of significant Islamic banking in the national banking system, on July 16, 2008 was enacted Law Number 21 of 2008 about Islamic Banking as the legal basis for Islamic banks in Indonesia.